The relationship between competencies acquired through Swiss academic sports science courses and the job requirements. Issue 1 (2nd January 2016) - Schlesinger, T.; Studer, F.; Nagel, S.
Abstract: In view of the changes in and growing variety of sports-related occupations, it is highly relevant for educational institutions to know how well the educational contents of their sport science courses meet the professional requirements. This study analyses the relationship between the competencies acquired through academic sports science courses and the requirements of the relevant jobs in Switzerland. The data for this empirical analysis were drawn from a sample of n = 1054 graduates of different academic sport science programmes at all eight Swiss universities. The results show that academic sport science courses primarily communicate sports-specific expertise and practical sports skills. On the other hand, most graduates consider that the acquisition of interdisciplinary competencies plays a comparatively minor role in sport science education, even though these competencies are felt to be an important requirement in a variety of work-related environments and challenges.